Comparative study on Pharmacokinetic Profiles of Chicken IgY to Horse IgG in Rabbits - ZHOU, ZHAOXIANG; WANG, JIAN; GAO, SONG; REN, HAO; XIE, WENYAN; THIRUMALAI, DIRAVIYAM; ZHANG, XIAOYING (Journal of the Hellenic Veterinary Medical Society, 2018)
Chicken IgY antibody has been extensively reported for various applications as an alternative to mammalian IgG. To evaluated the pharmacokinetics profile of chicken IgY in comparison with horse IgG. Chicken IgY antibody was prepared by immunizing the white leghorn chicken with tetanus toxoid (TT) and then extracted anti-TT-IgY from immune egg yolks by PEG-6000 extraction. The titer of anti-TT-IgY was determined by ELISA in order to select the hyper immune eggs for further extraction. Rabbits were injected with 300 μg/kg of Chicken IgY and horse IgG by intravenous (i.v.) and intramuscular (i.m.) administrations. Then, the concentrations of IgY and IgG in rabbit serum were determined using indirect ELISA. Pharmacokinetic parameters were estimated using non-compartmental analysis. IgY can reach higher concentration (Cmax= 4.54 mg/L after i.m. injection) within shorter time (Tmax= 0.12 h after i.m. injection) than IgG (Cmax= 3.99 ng/mL after i.m. injection; Tmax=0.11 h after i.m. injection), while the IgY lifespan (T1/2=26.98 h and 31.98 h after i.v. and i.m. administration, respectively) in the body was comparable with IgG (T1/2=27.94 h and 29.58 h after i.v. and i.m. administration, respectively). IgY might be a promising choice as an alternative to mammalian sourced antibodies.